How do social networks affect labor markets? - Ian Schmutte (IZA World of Labor, 2016)
Social networks, or “job-referral” networks, can help make labor markets become more efficient. Outside the firm, they help workers obtain employment after displacement and secure higher-paying jobs. They can also match highly-skilled workers to more productive employment. Inside the firm, referrals facilitate employment relationships that are more stable, productive, and profitable. In aggregate, referral networks help “grease the wheels” of a labor market that can be beset by a range of information problems. However, such networks can also be segmented along racial, ethnic, and socio-economic lines, which brings into question the effect they may have on inequality between and within different groups of workers.
Keywords: J01; J31; J42; J62; E24; D85; 330; referral networks; wages; unemployment; inequality; social interactions